2020
DOI: 10.1111/cdoe.12577
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries, periodontal disease and restorative dental care among Indigenous and non‐Indigenous groups in Brazil: A descriptive study

Abstract: Objective: To compare patterns of dental caries, periodontal disease and dental care among Indigenous and non-Indigenous Central-West Brazilian subpopulations. Methods: Data were from two population-based cross-sectional studies involving 5-, 12-, 15-19-and 35-44-year-olds. The first examined were the Guarani, Kaiowá, Terena and Kadiwéu Indigenous groups from Mato Grosso do Sul Brazilian state and the second comprised a non-Indigenous population. Mean numbers of sound teeth, decayed, missing and filled teeth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 24 publications
1
45
0
1
Order By: Relevance
“…No studies were excluded based solely on the assessment of methodological quality. Only 13 [Hallett and O'Rourke, 2002;Endean et al, 2004;Australian Institute of Health and Welfare, 2007;Brennan et al, 2007;Lawrence et al, 2008;Kapellas et al, 2014;Arrow, 2016;Jamieson et al, 2016a;Miranda et al, 2018;Shi et al, 2018;Simangwa et al, 2018;Haag et al, 2020;Arantes et al, 2021] studies of 43 answered "yes" for each critical appraisal question, achieving a score of 9 out of 9. The lowest score was 5, observed in studies by Jamieson et al [2007b] and Gowda et al [2009] as these studies failed to mention the sampling frame, methods for sampling participants, and sample size calculation.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…No studies were excluded based solely on the assessment of methodological quality. Only 13 [Hallett and O'Rourke, 2002;Endean et al, 2004;Australian Institute of Health and Welfare, 2007;Brennan et al, 2007;Lawrence et al, 2008;Kapellas et al, 2014;Arrow, 2016;Jamieson et al, 2016a;Miranda et al, 2018;Shi et al, 2018;Simangwa et al, 2018;Haag et al, 2020;Arantes et al, 2021] studies of 43 answered "yes" for each critical appraisal question, achieving a score of 9 out of 9. The lowest score was 5, observed in studies by Jamieson et al [2007b] and Gowda et al [2009] as these studies failed to mention the sampling frame, methods for sampling participants, and sample size calculation.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The lowest score was 5, observed in studies by Jamieson et al [2007b] and Gowda et al [2009] as these studies failed to mention the sampling frame, methods for sampling participants, and sample size calculation. Out of 43 studies, only 14 [Hallett and O'Rourke, 2002;Endean et al, 2004;Schroth et al, 2005;Australian Institute of Health and Welfare, 2007;Brennan et al, 2007;Lawrence et al, 2008;John et al, 2015;Arrow, 2016;Jamieson et al, 2016a;Miranda et al, 2018;Shi et al, 2018;Simangwa et al, 2018;Haag et al, 2020;Arantes et al, 2021] reported methods for sample size calculation or whether the sample size was adequate for the population of interest. Most studies described the study setting and participants in detail (95.3%).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations